2018
DOI: 10.1002/ecs2.2490
|View full text |Cite
|
Sign up to set email alerts
|

Epifaunal diversity patterns within and among seagrass meadows suggest landscape‐scale biodiversity processes

Abstract: Coastal seascapes can support high animal diversity and secondary productivity that attracts conservation interest and provides ecosystem services. Though the importance of spatial structure in marine habitats is well known, determining the dominant spatial scale for biodiversity patterns is an often‐overlooked dimension of the ecological and conservation value of seagrass meadows. We estimated biodiversity patterns at fine (0.28 m2), meadow and seascape scales to explore whether seagrass‐associated biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 65 publications
(177 reference statements)
3
24
1
Order By: Relevance
“…Spatial and temporal variability in dispersal, as well as variation in dispersal intensity, are likely primary drivers of alpha and beta diversity in seagrass ecosystems. There is, however, no direct evidence yet for how dispersal patterns could contribute to the spatial biodiversity patterns observed across seagrass meadows within regions (Carr et al 2011, Barnes & Ellwood 2012, Yamada et al 2014, Whippo et al 2018. Our study builds on previous work by Lee & Bruno (2009), which demonstrated that intensity and variability of grazer dispersal has a strong influence on grazer abundance, alpha diversity, and species composition.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Spatial and temporal variability in dispersal, as well as variation in dispersal intensity, are likely primary drivers of alpha and beta diversity in seagrass ecosystems. There is, however, no direct evidence yet for how dispersal patterns could contribute to the spatial biodiversity patterns observed across seagrass meadows within regions (Carr et al 2011, Barnes & Ellwood 2012, Yamada et al 2014, Whippo et al 2018. Our study builds on previous work by Lee & Bruno (2009), which demonstrated that intensity and variability of grazer dispersal has a strong influence on grazer abundance, alpha diversity, and species composition.…”
Section: Introductionmentioning
confidence: 66%
“…Hereafter, we use 'dispersal' synonymous with the grazer additions. Although the spatial scale at which grazer dispersal occurs remains an active research question, grazer density does vary at the scale of both meters and kilometers (Whippo et al 2018), which is likely a product of both grazer movement and grazer reproduction. However, we note that large pulses of grazers may also occur in seagrass communities due to local grazer blooms (Whippo et al 2018).…”
Section: Dispersal Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also showed some redundancy in presence/absence of the observed species among the study sites in Akkeshi (Momota & Nakaoka, ; Yamada et al, ) and other places (e.g., Whippo et al, ) as patches of eelgrass meadows are interconnected within a given system. Site‐specific community compositions can be determined not only by presence/absence of species but also by abundance of dominant species (Whippo et al, ). Therefore, the results for both abundance‐based and presence‐absence‐based RDA should be considered and that both salinity gradient and the amount of eelgrass habitats are the important components for determining the identities of species and their relative abundance.…”
Section: Discussionmentioning
confidence: 63%
“…While research in past decades has found evidence for direct and indirect influences of local characteristics such as habitat complexity (Orth et al 1984), primary biomass (Cébrian andDuarte 1998, Gullström et al 2012), and nutrient availability (Virnstein and Howard 1987) on faunal diversity and abundance, recent studies have focused more on regional scale or multimeadow processes such as dispersal (Whippo et al 2018, Lefcheck et al 2016, Stier et al 2019, Yeager et al 2019, and have found that the influence of local-scale factors are often overriden by regional patterns of inter-meadow connectivity (Lefcheck et al 2016, Stier et al 2019, Yeager et al 2019. This pattern has been attributed to relatively rapid life histories and high intermeadow dispersal in seagrass-associated organisms (Lefcheck et al 2016).…”
Section: Introductionmentioning
confidence: 99%